REPRESENTASI MASKULINITAS DALAM IKLAN JAMTANGAN.COM "AKSI JAGOAN" DI YOUTUBE - Lubis, Reissy Arta Oktavia; Abidin, Sholihul (SCIENTIA JOURNAL, 2022)
The advertisement Jamtangan.com "Aksi Jagoan" is an advertisement for a Seiko brand men's watch product. Advertising targets consumers with the concept of masculinity that packs the image of a man's strength. This advertisement favors the domination of male power over women. The concept of dominance in such advertising favors men in ordinate positions and women in subordinate positions. This study aims to find the myth of masculinity hidden in the advertisement Jamtangan.com "Aksi Jagoan". The research method used is a qualitative approach, the analysis used is the semiotics of Roland Barthes. Researchers used Pierre Bourdieu's Theory of Symbolic Violence, The results found from this study are representations of traditional masculinity with patriarchal culture obtained through screenshots of scenes that are considered to show a side of male masculinity that can be seen from the physical side of men such as being strong, having power over women, and being brave.